Chilean Rhubarb, Gunnera tinctoria (Molina) Mirb. (Gunneraceae): UHPLC-ESI-Orbitrap-MS Profiling of Aqueous Extract and its Anti-Helicobacter pylori Activity - Hebel-Gerber, Sonja; García-Cancino, Apolinaria; Urbina, Angélica; Simirgiotis, Mario J.; Echeverría, Javier; Bustamante-Salazar, Luis; Sáez-Carrillo, Katia; Alarcón, Julio; Pastene-Navarrete, Edgar (Frontiers in Pharmacology, 2021)
The full UHPLC-MS metabolome fingerprinting and anti-Helicobacter pylori effect of Gunnera tinctoria (Nalca) total extract (GTE) and fractions prepared from its edible fresh petioles were evaluated. The activity of G. tinctoria against H. pylori strains ATCC 45504 and J99 was assessed in vitro by means of agar diffusion assay, Minimum Inhibition Concentration (MIC), and Minimum Bactericidal Concentration (MBC), while killing-curve and transmission electronic microscopy (TEM) was conducted in order to determine the effect of the plant extract on bacterial growth and ultrastructure. Additionally, the inhibitory effect upon urease was evaluated using both the Jack Bean and H. pylori enzymes. To determine which molecules could be responsible for the antibacterial effects, tentative identification was done by ultra-high performance liquid chromatography coupled with high-resolution mass spectrometry (UHPLC-Q-Orbitrap®-HR-MS). Furthermore, the total G. tinctoria extract was fractionated using Centrifugal Partition Chromatography (CPC), giving four active fractions (1 to 4). It was determined that the crude extract and CPC fractions of G. tinctoria have a bactericidal effect being the lowest MIC and MBC = 32 μg/mL. In the killing-curves, fraction 1 acts faster than control amoxicillin. In the urease assay, F3 exhibited the lowest IC50value of 13.5 μg/mL. Transmission electronic microscopy showed that crude G. tinctoria extract promotes disruption and separation of the cellular wall and outer membrane detachment on H. pylori causing bacterial cell death.